A Study on the Reform and Innovation of College Economics Courses Based on Artificial Intelligence Technology - Qu, Na; Wang, Qinghui (Journal of Theory and Practice of Contemporary Education, 2023)
This paper explores the potential of utilizing artificial intelligence technology to reform and innovate the teaching of economics courses. Firstly, it points out the problems of excessive theory, lack of practicality, single teaching method, lack of frontier, and lack of interdisciplinary integration in the economics courses of traditional colleges and universities. Second, the feasibility of applying artificial intelligence in economics courses in colleges and universities is analyzed, and the role and technical performance of AI technology in the field of education are introduced. Finally, the technical, pedagogical, psychological, and ethical problems that may be faced by using AI technology in economics classrooms in colleges and universities are discussed, and corresponding solutions and strategies are proposed.